Smart Cities: Recent Trends, Methodologies, and Applications - Gavalas, Damianos; Nicopolitidis, Petros; Kameas, Achilles; Goumopoulos, Christos; Bellavista, Paolo; Lambrinos, Lambros; Guo, Bin (My University, 2017)
Worldwide forecasts indicate that the size and population of cities will increase even further. This immense growth will put a strain on resources and pose a major challenge in many aspects of everyday life in urban areas, such as the quality of services in the medical, educational, environmental, public safety, and security sectors, indicatively. Thus, novel methods of management must be put in place for these cities to continue to be sustainable. The wide adoption of pervasive and mobile computing systems gave rise to the term of “smart cities,” which implies the ability of sustainable city growth by leading to major improvements in city management and life in the above-mentioned sectors and other aspects such as energy efficiency, traffic congestion, pollution reduction, parking space, public safety, and recreation. This has been made possible in recent years due to the widespread availability of commodity low-power sensors, smart phones, tablets, and the necessary wireless networking infrastructure, which, along with technologies such as AI and management of big data, may be utilized to address the challenges of sustainable urban environments. In this special issue, articles regarding the use of technologies, methodologies, and applications for smart cities are invited. Authors are encouraged to submit articles mainly describing original research, presenting results that advance the state of the art and fuel more efforts in the future. Review articles are also welcome.
Keywords: Methodologies; Applications; Smart cities; Wireless Sensor Network